International labour office - Hardt, Hanno (Javnost (Ljubljana), 2005)
This article contains excerpts from a 1925/26 survey by the International Labour Office in Geneva, published in 1928, and involving journalistic organisations in 33 countries in Europe and the Americas. As a historical document the results of the survey anticipate and reinforce the development of a professional model of journalism - they call for adequate financial compensation, job security, and personal welfare for the individual journalist. As such the survey illustrates the plight of the rank and file after World War I in several countries.
Keywords: journalism; novinarstvo; novinarji; družbeni položaj; delovne razmere; delovni pogoji; življenjske razmere; 20.st.; Europe; Evropa